Penyalahgunaan Keadaan dalam Perjanjian Kerja Waktu Tertentu (PKWT) Alih Daya: Studi Perjanjian Kerja Pada PT. MD di Kota Medan - Geby Aviqa; Sunarmi; Leviza, Jelly; Harianto, Dedi (AL-SULTHANIYAH, 2025)
This research examines the abuse of conditions in the Specific Time Work Agreement (PKWT) by PT. MD in Medan City, with a focus on imbalances in contract clauses that are detrimental to agency workers. The problem formulation includes the legal principles of agreements, the exoneration clause in PT's PKWT. MD, forms of abuse of circumstances, and legal protection efforts. The method used is a normative method with a statutory and conceptual approach, through literature study and field research. Data analysis was carried out qualitatively based on interviews with PKWT workers at PT. MD in 2024. The research results found that the 2024 PKWT at PT. MD that the clauses in employment contracts contain exoneration clauses in the form of provisions that are contradictory and burdensome to workers, such as exoneration clauses and mandatory overtime without compensation. Abuse of circumstances occurs due to the dominance of the bargaining position of companies that take advantage of the uncertainty of workers' employment status to suppress their rights. This condition is exacerbated by weak legal supervision and the existence of regulations that do not fully accommodate the need for certainty and legal protection for PKWT workers at PT. MD.